2019
DOI: 10.1097/jpo.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Lycra Arm Sleeve on Glenohumeral Subluxation in Poststroke Hemiplegia—A Preliminary Study

Abstract: Objective: The primary aim of this preliminary study was to assess the effects of Lycra arm sleeves on the glenohumeral subluxation (Acromion-greater tuberosity distance) in people with post-stroke hemiplegia. A secondary aim was to explore patients' perceptions regarding the practicality of applying the Lycra arm sleeve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…This is in agreement with a previous study on people with stroke which showed a mean reduction of 0.24 cm immediately after the application of sleeve. 16 In that study an experienced rater was involved with ultrasound measurements of AGT distance. In contrast, in this study, a physiotherapy student trained in ultrasound measurements recorded AGT distance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is in agreement with a previous study on people with stroke which showed a mean reduction of 0.24 cm immediately after the application of sleeve. 16 In that study an experienced rater was involved with ultrasound measurements of AGT distance. In contrast, in this study, a physiotherapy student trained in ultrasound measurements recorded AGT distance.…”
Section: Discussionmentioning
confidence: 99%
“…18,26 One study involving three physiotherapy students reported excellent interrater reliability (ICC 0.79) of AGT measurements for the right shoulder in a relatively younger age group (mean age of 21 years SD 2). 16 Another recent study assessed interrater reliability of ultrasonographic measurements of AGT distance between experienced and novice raters in healthy individuals. This study found good (ICC 0.61) to excellent (0.87) interrater reliability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He educated the patients to wear the Lycra arm sleeve for seven hours per day for seven consecutive days. It was found that the decrease in mean acromion greater tuberosity distance would be due to wearing of Lycra arm sleeves which could be proved beneficial in management of shoulder subluxation in chronic stroke[38].A systemic review and meta analysis was done by H. Lee and S. M. Lim in Seoul, Republic of Korea in 2019 on evaluating evidence for the usefulness of acupuncture in lessening shoulder pain after stroke. They searched for many databases for controlled Trials till March 2015.…”
mentioning
confidence: 99%